Environmental Performance, Environmental Disclosure, dan Economic Performance: Perspektif Model Persamaan Simultan: Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar pada BEI - Usman Alfaruq; Usman Usman; Vicky Oktavia; Pradana Jati Kusuma (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the simultaneous relationship between environmental performance, environmental disclosure, and economic performance in manufacturing companies in the basic and chemical industries listed on the Indonesia Stock Exchange during the 2021–2023 period. This study applies a quantitative approach using the Three-Stage Least Squares (3SLS) method to 30 companies with a total of 90 observations. The results show that environmental performance has a significant positive effect on economic performance, while environmental disclosure has a significant negative effect on economic performance. Furthermore, economic performance has been shown to significantly influence both environmental performance and environmental disclosure. These findings indicate a reciprocal relationship between variables in supporting corporate sustainability. Overall, environmental performance is an important factor in improving economic performance, but environmental disclosure still creates cost pressures in the short term. This study implies that companies need to balance environmental responsibility and economic efficiency.